Comparison of suture materials for subcuticular skin closure at cesarean delivery - Tuuli, Methodius G.; Stout, Molly J.; Martin, Shannon; Rampersad, Roxane M.; Cahill, Alison G.; Macones, George A. (American journal of obstetrics and gynecology, 2016)
Subcuticular skin closure with suture after cesarean has been shown to result in lower rates of wound complications than with staple closure. However, the optimal choice of suture material for subcuticular skin closure is unclear. Vicryl (a braided multifilament synthetic suture; Ethicon, Somerville, NJ) and Monocryl (a monofilament synthetic suture; Ethicon) are the commonly used suture materials for subcuticular closure of transverse skin incisions after cesarean in the United States. Whereas in vitro and animal studies suggest multifilament suture materials may be associated with a higher risk of wound infection than monofilament sutures, clinical data on their relative effectiveness are limited. We sought to test the hypothesis that Vicryl is associated with a higher rate of wound complications than Monocryl. This is a secondary analysis of data from a randomized trial in which pregnant women undergoing scheduled or unscheduled cesareans were randomly assigned to preoperative skin preparation with either chlorhexidine–alcohol or iodine–alcohol. Women with low transverse skin incisions who were closed with either 4-0 Monocryl or 4-0 Vicryl were included in this analysis. Choice of suture material was at the discretion of the operating physician. The primary outcome was superficial or deep surgical site infection within 30 days after cesarean. Secondary outcomes were other wound complications. Outcomes were compared between the 2 groups using univariable and multivariable statistics. Of 1082 patients who had follow-up after discharge in the primary trial, 871 had subcuticular suture: 180 with 4-0 Vicryl and 691 with 4-0 Monocryl. Skin closure with Vicryl or Monocryl did not significantly differ between women allocated to chlorhexidine–alcohol or iodine–alcohol (51.1% vs 49.4%, P = .67). There was no significant difference in the risk of surgical site infection in women closed with Vicryl compared with Monocryl (11 [6.1%] vs 35 [5.1%]; P = .58; adjusted odds ratio, 1.23; 95% confidence interval, 0.60–2.49). Rates of other wound complications were also not significantly different. Risks of surgical site infection were similar with Vicryl and Monocryl closure in all subgroups assessed. The relative risks were not materially affected by whether diabetes or obesity was present, cesarean was scheduled or unscheduled, primary or repeat cesarean, or the subcutaneous layer was closed. Post hoc power analysis indicated that we had 80% power to detect >2-fold difference in surgical site infections. Subcuticular skin closure with 4-0 Vicryl is associated with comparable rates of surgical site infection and other wound complications as 4-0 Monocryl. While this is an observational study with the potential for selection bias and residual confounding, our results suggest physician preference is acceptable for choice of subcuticular suture material at cesarean.